Assessment of mental health trajectories before and after myocardial infarction, atrial fibrillation or stroke: analysis of a cohort study in Tromsø, Norway (Tromsø Study, 1994–2016). Issue 4 (1st April 2022) - Lorem, Geir Fagerjord; Opdal, Ida Marie; Wilsgaard, Tom; Schirmer, Henrik; Løchen, Maja-Lisa; Olsen, Ingrid Petrikke; Steigen, Terje; Rognmo, Kamilla
Abstract : Objectives: The increased survival rate of cardiovascular disease (CVD) implies a higher proportion of individuals who live with CVD. Using data from the Tromsø Study, we aimed to investigate mental health symptom trajectories before and after myocardial infarction, atrial fibrillation or stroke in a general population and to explore factors that contribute to the association. Design: Cohort study. Setting: Sample drawn from inhabitants of the municipality of Tromsø, Norway, who participated in the Tromsø Study (1994–2016). Participants: A total of 18 719 participants (52.3% women) were included, and of these 2098 (32.9% women) were diagnosed with myocardial infarction, 1896 (41.9% women) with atrial fibrillation and 1263 (42.9% women) with stroke. Primary outcome measures: Mental health symptoms were assessed using the Hopkins Symptom Checklist-10 and the Conor Mental Health Index. Results: The participants who were diagnosed with either myocardial infarction or stroke had a significant monotonous increase in mental health symptoms before myocardial infarction (p=0.029) and stroke (p=0.029) that intensified at the time of diagnosis. After the event, the study found a higher prevalence of mental health symptoms with a decline in symptom levels over time for myocardial infarction (p<0.001) and stroke (p=0.004), but not for atrial fibrillation (before: p=0.180, after: p=0.410). The risk of elevated mental health symptoms with myocardial infarction, atrial fibrillation and stroke was associated with sex (p<0.001), age (p<0.01), physical activity (p<0.001), diabetes (p<0.05) and other comorbidities (p<0.001). Conclusion: The study indicates that mental health problems among individuals with myocardial infarction, atrial fibrillation and stroke may have started to develop several years before the cardiovascular event and suggests that successful CVD rehabilitation may need to consider previous life factors. Future research is recommended to examine whether health promotion measures in a general population also create mental health resilience after a CVD event.